Multivariated variance analysis applied to biological experiments: An analysis with curves of rats teeth growth as influenced by colchicine - Curi, P. R.; Galvao Gomes, M. C.; Dias Costa, A. M D (My University, 1980)
The evaluation of the growth of incisor teeth of rats as influenced by colchicine (doses of 25, 50, 100 and 200 μg/kg) injected during 10 and 18 days is performed using a multivariated variance analysis, which allowed a global view of the results, showing that: there are differences in the growth of teeth of control group (untreated rats) and those treated with colchicine, in the measurements made at the 4th, 7th and 10th days of experiment); there is no difference in the growth of the teeth between the groups treated during 10 and 18 days, except in the measurements made at the 7th day; there is no influence of the doses of colchicine in the group treated during 10 days and in the group treated during 18 days - only at the 7th day is observed an influence of the doses used; and there was no significant interaction between treatment and days of measurement, showing the similarity of the groups during the experiment.
Keywords: colchicine; animal experiment; rat; therapy; tooth; tooth development